GROMPOL DAN SIDO ASIH SENSASI IMPIAN PERADUAN - Ms. Widarwati (SURYA SENI, 2008)
Grompol and Sido Asih Royal Bed Sensation. Batik is an art-work comes from native Indonesia culture that has high value. There are many philosophy values inside it, according to each motif ornaments and elements. The decreasingnumber of batik users has became a concern for the writer, so that an idea emerges from it to use batik as a source of inspiration in an art-work making.Sido Asih and Grompol are kinds of batik’s motif from a lot of motifs that have speciﬁ c philosophical meaning. “Grompol” means to gather around with “Sido Asih” means to be loved or love and affection have been combined nicely as the elements for royal bed in a bridal room which are implemented on somematerials such as: bed sheet, primisima (shantung) dacron and siphon cloth, beside the other elements like wooden carving and cendani bamboo that also have royal their own meanings. It was expected that the philosophy inside this artworkbecome the reﬂ ection of the bridal couple’s life in the future in wading across their life.From many processes that have been done, then it was produced an art work that has its own uniqueness, that is the combination between the modern and glamorous elements represented by tassels and curtains with traditional, superiorand supreme values on batik cloth. The basic of creation of this art-work uses textile craftsmanship, especially batik and quilting techniquesKeywords: batik, grompol, sido asih, and royal bed